Práticas pedagógicas na Educação Infantil com arte afro-brasileira: valorização da diversidade cultural mediada pela literatura infantil - Melo, Laura Oliveira de Araújo (Universidade Federal de São Carlos, 2026)
This work aims to investigate possibilities for pedagogical action with Afro-Brazilian and African arts in Early Childhood Education, in a meaningful and appropriate way for young children, considering their specificities, forms of expression, and the relationships they build in the school environment. Based on this objective, it seeks to answer the following research question: how can Afro-Brazilian and African arts be incorporated into Early Childhood Education in a way that is sensitive to the characteristics of early childhood, valuing the multiple forms of expression of young children and their interactions in the educational context? Linked to this problem, the study seeks to understand how teaching practice can develop pedagogical strategies aimed at valuing cultural and ethno-racial diversity, incorporating Afro-Brazilian art as a path to promoting anti-racist education from the earliest years of life. It also seeks to reflect on its contributions to strengthening the self-esteem of Black children, to respecting differences, and to valuing ethno-racial identities in childhood. To answer the research question, this work articulates legal, conceptual, and pedagogical contributions that underpin the inclusion of Afro-Brazilian and African arts in Early Childhood Education and highlight the importance of teacher training for the effective implementation of this proposal. Laws No. 10.639/2003 and No. 11.645/2008 are analyzed, as well as the National Curriculum Guidelines for Education on Ethnic-Racial Relations and for the Teaching of Afro-Brazilian and African History and Culture, which establish the mandatory teaching of African, Afro-Brazilian, and Indigenous history and culture, including their artistic expressions. The study presents a reflection on the concept of Afro-Brazilian art, its relevance to the formation of young children's identities, and the challenges and possibilities of its implementation in Early Childhood Education, understanding teacher education as a fundamental condition for the construction of pedagogical practices committed to racial equity. In the final part of this work, three works of children's literature addressing the theme of Education for Ethnic-Racial Relations (ERER) are analyzed. Based on each analysis, a pedagogical action involving artistic experiences with children is proposed. The proposals are grounded in Ana Mae Barbosa's Triangular Approach, which articulates three inseparable axes: artistic creation; the reading and appreciation of images, works, and cultural productions; and the historical, social, cultural, experiential, and subjective contextualization of artistic manifestations. In this way, the aim is to offer support for pedagogical practices that promote children's encounter with Afro-Brazilian art in a sensitive and meaningful way. From this perspective, children's literature is understood as a mediator of children's encounter with Afro-Brazilian art, fostering aesthetic, cultural, and identity experiences from early childhood.
Pedagogical practices in early childhood education with Afro-Brazilian art: valuing cultural diversity through children's literature
Keywords: Arte afro-brasileira; Afro-Brazilian art; Diversidade cultural; Cultural diversity; Formação de professores; Teacher education; Educação infantil; Early childhood education; Prática pedagógica; Pedagogical practice; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; 4. Educação de Qualidade